2015
DOI: 10.1039/c5ta03614c
|View full text |Cite|
|
Sign up to set email alerts
|

BaTiO3–BiYbO3perovskite materials for energy storage applications

Abstract: Novel perovskite-type of (1-x)BaTiO 3 -xBiYbO 3 solid solutions with x = 0.00 ~ 0.20 were synthesized by conventional solid-state reaction methods. A systematic structural change from the ferroelectric tetragonal to pseudo-cubic phase was observed at about x = 0.050 ~ 0.051 at room temperature. Dielectric measurements revealed a gradual change from normal ferroelectric behavior to highly diffusive and dispersive relaxor-like characteristics, where the phase transition temperature shifted to higher temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
169
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 423 publications
(179 citation statements)
references
References 59 publications
(96 reference statements)
10
169
0
Order By: Relevance
“…The temperature-dependent dielectric spectroscopies of the BFSTO films exhibit broadened dielectric peaks and frequency dispersion (Supplementary Fig. 4), further evidencing the RFE characteristics 14 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The temperature-dependent dielectric spectroscopies of the BFSTO films exhibit broadened dielectric peaks and frequency dispersion (Supplementary Fig. 4), further evidencing the RFE characteristics 14 .…”
Section: Resultsmentioning
confidence: 63%
“…First, the spontaneous polarization P s of BTO is only 26 μC cm −2 , much lower than that of PbTiO 3 (~80 μC cm −2 ) 13 . Second, as BTO-based RFEs bears low Curie temperatures T c (<100 °C), the deterioration of their ferroelectricity and energy storage performance can be evident at elevated temperatures 14,15 . To address these problems, we focus on a new lead-free system, namely, BiFeO 3 (BFO), which has been acknowledged to be a promising alternative of lead-based dielectrics/ferroelectrics with a large P s of ~100 μC cm −2 and a high T c of 830 °C 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The ε′ gradually increases with increasing of sintering temperature from 25 to 1050 °C. The ε′ values are also significantly higher than other perovskite composites [13]. At the interface of semiconducting grain and insulating grain boundary, the charge carriers are accumulated and possessed an increase in dielectric constant [4].…”
Section: Resultsmentioning
confidence: 99%
“…They are basically perovskite M 2+ TiO 3 in structure, and face-centered cubic (FCC) (if M = Ca, Ba, and Sr) or trigonal (if M = Fe, Co, Ni, Mn, and Mg), depending on chemical composition [11,12]. Lead (Pb) free perovskite materials have been investigated to be used in many energy storage applications [13,14]. The perovskite calcium titanate (orthorhombic or monoclinic CaTiO 3 ) and geikeilite magnesium titanate (rhombohedral MgTiO 3 ) are being used as attractive materials in many ceramic coating industries [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…So, there are two possible routes to improve the energy-storage density of AFE and FE ceramics for energy storage applications: One is to enhance the BDS for high E and another is to increase the limit of integration by enlarging the difference between the P max and P r . For the first route, it was found that AFE ceramic ( [17][18][19][20][21] It indicated that partial occupancy of Bi 3þ at the A site of the perovskite compound could effectively improve the energy storage properties. As a promising candidate system, relaxor ferroelectrics BaTiO 3 (BT)-based ceramics play a key role in the area of energy density capacitors because of their low P max , high P r , and low loss.…”
mentioning
confidence: 99%